Desain Dan Simulasi Mesin Sortir Biji Kopi Kering Dengan Sistem Penggerak Engkol - Fatih, Ahmad; Kabib, Masruki; Hudaya, Akhmad Zidni (JURNAL CRANKSHAFT, 2021)
There are still many coffee beans processed by home industry that still do not have a coffee bean sieving machine, and the products produced are still of many sizes that do not meet the standard, so the selling power of the salt is cheap. To solve this problem, a coffee bean sieving machine will be designed with a home industry scale capacity of 300 kg / hour.The design of this sieving machine aims to be able to separate the size of coffee beans that meet the standards, so that it can produce consumption coffee beans with a size that meets SNI consumption coffee beans, This sorting machine is specifically used for robusta coffee beans. The design of the tool uses 3 aluminum containers arranged in stages. Each container has holes of different diameters, namely 7 mm, 5 mm and 3 mm. and it is expected that this machine can sort 300kg / hour.